In Situ Polymer‐Imprinted Architecture of Textured Perovskite Single‐Crystal Sheets for Ultraweak‐Light Photodetection. Issue 4 (15th December 2022) - Li, Panpan; Huang, Wenjun; Xu, Wenchao; Wei, Xiangfeng; Chen, Yudan; Meng, Fancheng; Deng, Weiqiao; Liu, Jiehua
Abstract: A facile double flexible interfacial imprinting method is reported to obtain the cubic single‐crystal CH3 NH3 PbBr3 sheets with in situ polymer patterns by capillary effect. The imprinted CH3 NH3 PbBr3 sheets offer good crystallinity and light‐trapping structure. As a result, the textured single‐crystal photodetector exhibits the superior responsivity of 63.0 A W −1, external quantum efficiency of 1.50 × 10 4 %, and detectivity D * of 8.12 × 10 12 Jones under 520 nm irradiations with a weak power density of 0.54 µW cm −2 at 3 V, which are more than 4200% and 80000% higher than those of the photodetector based on single‐crystal bulk and polycrystalline film, respectively. The exciting ultraweak‐light photoelectric performance is achieved due to the good light trapping and high carrier collection. Especially, the photodetector also exhibits excellent self‐powered performance. Abstract : Imprinted cubic single‐crystal CH3 NH3 PbBr3 sheets are synthesized by a facile double flexible polymer interfacial imprinting method with in situ polymer patterns by capillary effect. The textured single‐crystal‐based photodetector exhibits exciting photoelectric performance and excellent self‐powered performance due to high crystallinity, good light trapping, and carrier collection.